2016
DOI: 10.1016/j.actbio.2015.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Stiffness, strength and adhesion characterization of electrochemically deposited conjugated polymer films

Abstract: Conjugated polymers such as poly(3,4-ethylenedioxythiphene) (PEDOT) are of interest for a variety of applications including interfaces between electronic biomedical devices and living tissue. The mechanical properties, strength, and adhesion of these materials to solid substrates are all vital for long-term applications. We have been developing methods to quantify the mechanical properties of conjugated polymer thin films. In this study the stiffness, strength and the interfacial shear strength (adhesion) of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 33 publications
6
32
0
Order By: Relevance
“…The decrease in film stiffness in DI water is directly related to the swelling of the polymer. Our results are in agreement with those reported by Okuzaki and Ishihara (1.4 ± 0.6 GPa), Lang et al (1.3 ± 0.6 GPa), and Qu et al (2.6 ± 1.4 GPa) . These results suggest that GOPS is a versatile additive that can be used not only to improve the aqueous stability of films but also to modify their elasticity.…”
Section: Resultssupporting
confidence: 93%
“…The decrease in film stiffness in DI water is directly related to the swelling of the polymer. Our results are in agreement with those reported by Okuzaki and Ishihara (1.4 ± 0.6 GPa), Lang et al (1.3 ± 0.6 GPa), and Qu et al (2.6 ± 1.4 GPa) . These results suggest that GOPS is a versatile additive that can be used not only to improve the aqueous stability of films but also to modify their elasticity.…”
Section: Resultssupporting
confidence: 93%
“…The large PEDOT aggregate protrudes from the surrounding PSS matrix. Mapping of elastic modulus reveals that the PEDOT aggregate is softer than the surrounding PSS matrix by ≈3 GPa, which is consistent with previous reports …”
Section: Resultssupporting
confidence: 92%
“…The interface between high‐shear modulus and low‐shear modulus regions exhibited the largest viscoelastic change with humidity, which is consistent with mechanisms proposed by others in which adsorption leads to formation water meniscus layers that disrupt hydrogen bonding and facilitate solvation of ambient gas . The results are consistent with elastic moduli of PEDOT and PSS in dry and wet states reported by others, including Lang et al who showed that PEDOT:PSS elastic modulus decreased from 2.8 to 0.9 GPa when RH increased from 23% to 55% …”
Section: Resultssupporting
confidence: 90%
“…Typical tensile strain at fracture for conducting polymers is less than 10% . The fracture tensile strain of PEDOT film was found to be around 2% . It has been reported that the doping of larger dopant can make the conducting polymer more brittle .…”
Section: Micromechanics For Stretching Of Conducting Elements On Elasmentioning
confidence: 98%